STRATEGIS AUSTRALIA DALAM KERJA SAMA REGIONAL ASIA PASIFIK - Safira Oktaviani; Dedi Irwanto; Alif Bahtiar Pamulaan (Prodi Pendidikan Sejarah FKIP USI, 2025)
This research aims to analyze Australia's strategic role in establishing and strengthening regional cooperation in the Asia Pacific region. As a developed country geographically located close to Asian countries, Australia has significant political, economic and security interests in the region. This research uses a qualitative approach with a literature study method, analyzing various foreign policy documents, international organization reports, and scientific articles related to Australia's relations with Asia Pacific countries. The results show that Australia plays an active role in various regional forums such as the ASEAN Regional Forum (ARF), East Asia Summit (EAS), and APEC. This strategic role includes supporting regional security stability, enhancing economic cooperation, and inclusive multilateral diplomacy. Australia also balances relations with major powers such as the United States and China, in order to maintain its influence and interests in the region. The main conclusion of this study is that Australia plays an important role as a link between the Western and Asian worlds, and its contribution to Asia Pacific regional cooperation is crucial to the stability and progress of the region.